Saneamento e a dinâmica da sazonalidade hídrica: um estudo de caso em área de várzea, Iranduba/AM - Silva, Ketlen Mariana Veras da (Brasil, 2024)
This work addresses the issue of basic sanitation in flooded areas, highlighting the difficulties residents face and directly impacting the riverside population's quality of life and health. The study's main objective is to evaluate the components of basic sanitation in relation to the dynamics of water seasonality in a riverside community in the municipality of Iranduba/AM. To this end, it was necessary to characterize the area regarding the water periods that affect the region, describe the basic sanitation scenario in the community, survey the sanitation solutions applied by residents, and point out potential solutions applicable to the local reality. A descriptive research was then carried out with a qualitative-quantitative approach with a case study of the chosen area between November 2023 and March 2024. The study area comprises a community settled in the floodplain, composed of 125 registered families who live in floating houses suspended on stilts or in wooden or masonry buildings. Interview forms were applied to 17 families, and the researcher complemented them with participatory observation. The selection of the community considered its location, especially the variation in the level of the Solimões River, between 17 and 21 meters in altitude. The results revealed that 59% of the homes visited do not have a bathroom as a constituent part of the home, including those that have improvised toilet facilities in the external area of the land and those that do not have one and carry out open defecation. In the local flood scenario, external bathrooms are inaccessible. The solution adopted is defecation directly into the watercourse, mainly affecting the 38% of the sample that supplies water directly from the Solimões River. In the water supply area, around 35% favor the recent form of water supply. Even though it is located in the city's Center neighborhood, 82% of those interviewed stated that there are no records of solid waste collection in the community. Alternatively, 76% of respondents reported burning waste in their backyards, except during floods, when it occurs inside homes. Potential solutions were raised based on the needs of residents, analyzing speeches, form responses, and cultural aspects of the region. In this way, it was possible to conclude that the study was carried out to obtain data beyond the quantitative axis, seeking to present cultural and regional characteristics and the adaptations of residents to the conditions of the Amazon biome. Such data are essential to guide future studies aimed at improving rural sanitation in flooded areas and, consequently, promoting public health.